Smart specialization: a possible strategy for Costa Rica (National Administration Journal, 2020)
Innovation is a strategic factor in the economic, social and cultural development of the country aiming at reaching high levels of growth and well-being for its population.For over 20 years the Basque Country has been developing an innovation model with ecosystem stakeholders through the Smart Specialization Strategy, which makes it a European reference and an innovation hub.The implementation of the “smart” strategies involves integrated agendas for territorial economic transformation, political support and investments for development through technological and research centers, R&D units, strategic clusters and universities as key actors generating knowledge.
Keywords: Innovation; RIS3 strategy; economic development; regional strategy; innovation hubs